2023
DOI: 10.1136/openhrt-2023-002256
|View full text |Cite
|
Sign up to set email alerts
|

Serum B-type natriuretic peptide levels (BNP) can be used as a predictor of complications in patients undergoing non-cardiac surgery: a prospective observational study

Abstract: ObjectivesWorldwide, an estimated 10 million adults annually experience significant myocardial injury after non-cardiac surgery. Our aim is to assess whether preoperative and postoperative serum B-type natriuretic peptides levels (BNP) could be used as a predictor of postoperative complications in hypertensive and diabetic patients post non-cardiac surgery.DesignProspective observational study.SettingSingle tertiary-care centre in northern India.ParticipantsThis study included 260 adult participants with known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…19 Xiang et al 20 found that serum BNP is significantly overexpressed in patients with chronic heart failure, significantly correlated with the severity of the patient's heart function classification, and is an independent risk factor for chronic heart failure, serving as a serum biomarker for the disease. Singh et al 21 discovered that in patients undergoing non-cardiac surgery with hypertension and diabetes, preoperative and postoperative serum BNP levels are significantly elevated, making BNP an important predictor for perioperative and postoperative complications, hospital stay, and mortality rates in these patients. Zheng et al 22 found that BNP is significantly overexpressed in the serum of patients with acute pulmonary embolism combined with pulmonary hypertension, and its expression increases with the severity of pulmonary hypertension, having high diagnostic value for the disease, and correlates positively with disease severity, serving as a predictive marker for the severity of the condition.…”
mentioning
confidence: 99%
“…19 Xiang et al 20 found that serum BNP is significantly overexpressed in patients with chronic heart failure, significantly correlated with the severity of the patient's heart function classification, and is an independent risk factor for chronic heart failure, serving as a serum biomarker for the disease. Singh et al 21 discovered that in patients undergoing non-cardiac surgery with hypertension and diabetes, preoperative and postoperative serum BNP levels are significantly elevated, making BNP an important predictor for perioperative and postoperative complications, hospital stay, and mortality rates in these patients. Zheng et al 22 found that BNP is significantly overexpressed in the serum of patients with acute pulmonary embolism combined with pulmonary hypertension, and its expression increases with the severity of pulmonary hypertension, having high diagnostic value for the disease, and correlates positively with disease severity, serving as a predictive marker for the severity of the condition.…”
mentioning
confidence: 99%